The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2003
DOI: 10.1002/elps.200305450
|View full text |Cite
|
Sign up to set email alerts
|

Simultaneous chiral discrimination of multiple profens by cyclodextrin‐modified capillary electrophoresis in normal and reversed polarity modes

Abstract: Simultaneous enantioseparations of nine profens for their accurate chiral discrimination were achieved by capillary electrophoresis (CE) in the normal polarity (NP) mode with a single cyclodextrin (CD) system and in the reversed polarity (RP) mode with a dual CD system. The single CD system in the NP mode employed heptakis(2,3,6-tri-O-methyl)-beta-cyclodextrin (TMbetaCD) added at 75 mM-100 mM 2-(N-morpholino)ethanesulfonic acid buffer (pH 6.0) as the optimum run buffer. The dual CD system operated in the RP mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 32 publications
(72 reference statements)
1
11
0
Order By: Relevance
“…The electrokinetic chromatography method seemed to be acceptable at an analytical time of 10 minutes (Jabor et al, 2002). The highperformance capillary electrophoresis method has also been successfully developed for chiral determination of ketoprofen and flubiprofen (Glowka and Karazniewicz, 2004), and for simultaneous discrimination of multiple profens (La et al, 2003). Considering the same molecular structures of 2-arylpropionic acid derivatives, methods developed for one of them could be applied to others after minor modification.…”
Section: Enantioselective Analysis Methodsmentioning
confidence: 97%
“…The electrokinetic chromatography method seemed to be acceptable at an analytical time of 10 minutes (Jabor et al, 2002). The highperformance capillary electrophoresis method has also been successfully developed for chiral determination of ketoprofen and flubiprofen (Glowka and Karazniewicz, 2004), and for simultaneous discrimination of multiple profens (La et al, 2003). Considering the same molecular structures of 2-arylpropionic acid derivatives, methods developed for one of them could be applied to others after minor modification.…”
Section: Enantioselective Analysis Methodsmentioning
confidence: 97%
“…This information is the basic knowledge needed for a rational development of the appropriate method for the resolution of racemate. In particular, cyclodextrins (CDs), which are chiral macrocycles characterized by a hydrophobic inner cavity and a outer hydrophilic surface, have been used as chiral selectors for the separation of IBP enantiomers [12][13][14][15]. In this sense, a 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 shown that, in liquid phase, (S)-IBP forms more stable inclusion complexes with hydroxyprophyl-β-cyclodextrin (HP-β-CD) as compared with (R, S)-IBP [16], as well as chiral discrimination was studied in water by NMR analysis.…”
Section: Introductionmentioning
confidence: 99%
“…The CE system was equipped with a photodiode array detector, an automatic injector, and an uncoated fused silica capillary (Polymicro Technologies, AZ, USA; 502 mm × 50 µm I.D. ; 400 mm to detector window) installed inside a fluid‐cooled column cartridge . Samples ( ~ 3.2 nL) were introduced in pressure injection mode for 3 s at 3.4 kPa into the capillary.…”
Section: Methodsmentioning
confidence: 99%
“…Furthermore, the chiral profiling analysis of eight β‐blockers in a single run is attempted with dual chiral selectors of uncharged DM‐β‐CD and (+)‐ or (−)‐18‐C‐6‐TA in a chiral CE system of normal polarity mode, respectively. The present method is optimized for the overall procedure and validated for accurate peak identification and chiral discrimination by crosschecking for relative migration times (RMTs) and EMOs of the investigated ( S )‐ and ( R )‐β‐blockers …”
Section: Introductionmentioning
confidence: 99%